Peran Kepala Sekolah Dalam Memastikan Keberhasilan Perencanaan Dan Eksekusi Rapat Madrasah Tsanawiyah Islamiyah Jalan Suluh - Rheina Sayla; Zahra Nabila Iqbal; Eka Satya (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This research aims to examine the role of the school principal in planning and implementing meetings at Madrasah Tsanawiyah Islamiyah Jalan Suluh using qualitative and quantitative approaches. The school principal plays a central role in setting relevant meeting agendas, facilitating constructive discussions, and creating an inclusive and collaborative meeting environment. Through in-depth interviews, participant observation, and document analysis, this research found that school principals face the main challenges in the form of limited time and differences of opinion between meeting participants. However, this challenge was successfully overcome through effective facilitation techniques and a participatory approach to decision making. Quantitative analysis revealed that the majority of meeting participants were satisfied with the planning and implementation process of the meeting, with a clear agenda and decisions that could be implemented well. The level of satisfaction of meeting participants shows a positive relationship with the clarity of the meeting agenda, confirming the importance of transparency and effective communication. Active participation from all stakeholders has also been proven to contribute to meeting effectiveness. This research provides several recommendations to increase the effectiveness of school meetings, including: increasing training for school principals in the field of meeting management and leadership, developing a more systematic feedback mechanism from meeting participants, and using technology to increase the efficiency of planning and implementing meetings. It is hoped that the implementation of these recommendations can strengthen the role of school principals in leading meetings, which will ultimately contribute to improving the quality of school management and education in Indonesia. It is also hoped that the results of this research can become a reference for other educational institutions in an effort to improve the quality of meeting management and effective decision making.